(untitled) (Jurnal De Jure Muhammadiyah Cirebon, 2020)
Abstract Law of the Republic of Indonesia Number 11 Year 2012 Concerning the Criminal Justice System for Children born in 2012, came into force promulgated on July 31, 2014 replacing Law Number 3 of 1997 concerning the Juvenile Court. This law is predicted to be able to solve various problems of Children in Conflict with Law (ABH) which have not been able to be completed by the previous regulation by prioritizing the principles of Restorative Justice. In the Act specifically discussed about Diversion even clarified by Government Regulation Number 65 of 2016 concerning the Implementation of Diversity and Handling of Children under 12 years of age. Violent crime / brawl committed by a group of young people in the city of Cirebon is quite high at the end of 2019 until entering 2020, very unsettling because injured victims even died. The legal settlement of the perpetrators proven to have committed the criminal act of mistreatment or brought sharps was legally processed up to the trial, while the children who participated in the group were only arrested and subsequently returned to the family. This treatment of followers / participants is less effective for coaching and there is a tendency to repeat the criminal offense. Diversity that has been accommodated in the SPPA Law is expected to be able to answer this problem by involving several competent institutions for assistance and guidance for ABH.